Pengaruh Working Capital to Total Assets, Debt to Equity Ratio, Total Assets Turnover dan Operating Profit Margin Terhadap Pertumbuhan Laba - Sugandi, Anton; Kaharti, Eni (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2023)
The purpose of this study was to determine the effect of working capital-to-total assets, debt-to-equity ratio, total asset turnover, and operating profit margin on profit growth. The population used are mining companies listed in the Indonesia Stock Exchange 2017-2021 period which amounts as much 53 companies. The sampling technique used is purposive sampling and obtained by amount as much 37 companies multiplied by 5 years, so the total sample amount as much 185 companies. The analysis technique used is multiple linear regression analysis with SPSS Version 24. The hypothesis test uses the t-statistic level of significance of 5%. The result shows that: WCTA has a negative and significant effect on growth profit, so H1 is rejected and H0 is accepted. DER has a negative and significant effect on growth profit, so H2 is accepted and H0 is rejected. TATO and OPM have positive and significant effects on growth profit, so H3 and H4 are accepted and H0 is rejected. Based on the value adjusted R2, it shows that the contribution of variable WCTA, DER, TATO, and OPM can be explained by a growth profit is 0.604 or 60,4%. The remaining 0.396  or  39,6%  was caused by other variables which were not examined in this study.